2018
DOI: 10.1075/ttmc.00007.nav
|View full text |Cite
|
Sign up to set email alerts
|

The use of audio description in foreign language education

Abstract: Audio description (AD) is a type of audiovisual translation (AVT) used for making video content accessible to the blind and visually impaired. Over the last decade, the pedagogic potential of AVT in foreign language learning (FLL) has gained increasing recognition by experts. However, AD as a didactic tool in FLL is an innovative area that has received very little attention so far, despite its significant potential for language learners. In addition, many experts in Applied Linguistics have shown a growing int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 18 publications
2
12
0
6
Order By: Relevance
“…Pair and individual work were the most appreciated by the participants. Although it was not the aim of the study, in the final group interview, the researchers observed an improvement in the participants' oral skills in terms of fluency and pronunciation which goes in line with previous studies (Ibáñez Moreno & Vermeulen, 2015a;Navarrete, 2018;Talaván & Lertola, 2016).…”
Section: Audio Descriptionsupporting
confidence: 87%
See 2 more Smart Citations
“…Pair and individual work were the most appreciated by the participants. Although it was not the aim of the study, in the final group interview, the researchers observed an improvement in the participants' oral skills in terms of fluency and pronunciation which goes in line with previous studies (Ibáñez Moreno & Vermeulen, 2015a;Navarrete, 2018;Talaván & Lertola, 2016).…”
Section: Audio Descriptionsupporting
confidence: 87%
“…Two questionnaires were also administered to collect students' perceptions of the two oral activities (podcast and AD). Navarrete (2018) acknowledges the limitations of the study; however, she considers that the positive responses of the learners to the AD task are encouraging and set the basis for further investigation. Calduch and Talaván (2018) investigate whether AD can foster stylistic richness by enhancing vocabulary acquisition.…”
Section: Audio Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teachers can use a variety of audiovisual programmes, as well as exploit different types of videos to prompt students to produce their own subtitling (captions, interlingual, reversed) and revoicing (voiceover, dubbing). Tasks on media accessibility practices, such as audio description (AD) for the blind and the partially sighted audiences and subtitling for the deaf and hard of hearing (SDH), are becoming more common nowadays too (Navarrete, 2018;Talaván, 2019). Nonetheless, all these educational methods must respond to previously established objectives.…”
Section: Audiovisual Translation and Media Accessibility Practices: R...mentioning
confidence: 99%
“…The accelerating pace of change has put tremendous pressure on instructors who had no choice but to cope with the digital transformation and the technical know-how required in order for them to survive and not be left behind. Therefore, it is of paramount importance for teachers to infuse technology into teaching and at all levels of education (Adcock, 2008;Blyth, 2018;Navarrete, 2018).…”
Section: Second and Foreign Language And Technologymentioning
confidence: 99%